Analisis Pengaruh Perputaran Aset, Struktur Modal dan Kebijakan Deviden terhadap Kinerja Keuangan pada Perusahaan Sektor Perbankan yang Terdaftar di BEI Periode 2019-2023 - Ponco Aji Pamungkas; Suprihatmi Suprihatmi (Universitas 45 Surabaya, 2024)
This research uses quantitative data consisting of TATO, DER, DPR and ROA sourced from www.idx.com. The data collection technique in this research is poroposive sampling using secondary data. The sample in this research was 45. The data analysis technique used descriptive analysis, namely in the form of multiple linear regression analysis, t test, F test, and coefficient of determination test. The t test results show that asset turnover has no significant effect on financial performance because it has a significant value of 0.069 > 0.05. Capital structure has no significant effect on financial performance because it has a significant value of 0.456 > 0.05. Dividend policy has a significant effect on financial performance because it has a value of 0.002 < 0.05. The results of the F test show a significant value of 0.002 < 0.05, meaning that there is an independent influence, namely asset turnover, capital structure and dividend policy on the dependent variable, namely financial performance. The result of the coefficient of determination is 25.4%, meaning that the influence of the independent variables, namely asset turnover, capital structure and dividend policy on the dependent variable, namely financial performance, is large, the remaining 74.6% is influenced by other factors outside the variables studied.